Peran Kelompok Masyarakat (KUBE Lumbung Sinergi) Dalam Meningkatkan Kesejahteraan Warga Desa Bulakan Sukoharjo Jawa Tengah - sarjiyanto, sarjiyanto (EP FEB UNS, 2017)
This study uses grounded theory method, in which the approach taken is by field work observations. The observation instruments used in the field is in-depth interviews with list of questions. The results showed that the effectiveness of the role of community groups in an effort to improve the welfare center for the furniture industry is very high; it is seen from the indicators of economic well-being of the community members and the increased ownership of assets / capital investment for reproduction. According to the theory of success in accumulating assets and undertake reinvestment by community groups, there is a characteristic or a form of social entrepreneurship. The community group’s role effectiveness is also demonstrated by the increase in the group members' productivity. This is in line with Input-Process-Output Model theory of Strategic Entrepreneurship, which stated that community groups successfully processes input and outputs which provide profits for the members, their own institution and social groups. While the barriers faced by community groups in the effort improving the welfare for the furniture industry are: internal and external. Internal obstacles are the low creation and innovation as the members' low formal education background; moreover transparency lack is also a source of internal constraints for community groups. The external constraint is due to negative stereotype against community groups and the post power syndrome of senior public figures.